MEMS and Nanotechnology, Volume 4 Proceedings of the 2011 Annual Conference on Experimental and Applied Mechanics - Proulx, Tom. (2011)
MEMS and Nanotechnology represents one of eight volumes of technical papers presented at the Society for Experimental Mechanics Annual Conference & Exposition on Experimental and Applied Mechanics, held at Uncasville, Connecticut, June 13-16, 2011. The full set of proceedings also includes volumes on Dynamic Behavior of Materials, Mechanics of Biological Systems and Materials, Mechanics of Time-Dependent Materials and Processes in Conventional and Multifunctional Materials; Optical Measurements, Modeling and, Metrology; Experimental and Applied Mechanics, Thermomechanics and Infra-Red Imaging, and Engineering Applications of Residual Stress.
Integrated Process Feasibility of Hard-mask for Tight Pitch Interconnects Fabrication -- Thermoelectric Effects in Current Induced Crystallization of Silicon Microstructures -- Evaluation of Resistance Measurement Techniques in Carbon Black and Carbon -- Nano-tubes Reinforced Epoxy -- A Nano-tensile Tester for Creep Studies -- The Measurement of Cyclic Creep Behavior in Copper Thin Film Using Microtensile Testing -- New Insight Into Pile-Up in Thin Film Indentation -- Measuring Substrate-independent Young's Modulus of Thin Films -- Analysis of Spherical Indentation of an Elastic Bilayer Using a Modified Perturbation Approach -- Nano-indentation Studies of Polyglactin 910 Monofilament Sutures -- Analytical Approach for the Determination of Nanomechanical Properties for Metals -- Advances in Thin Film Indentation -- Cyclic Nanoindentation Shakedown of Muscovite and its Elastic Modulus Measurement -- Assessment of Digital Holography for 3D-shape Measurement of Micro Deep Drawing Parts in Comparison to Confocal Microscopy -- Full-field Bulge Testing Using Global Digital Image Correlation -- Experimental Investigation of Deformation Mechanisms Present in Ultrafine-grained Metals -- Characterization ofá a Variation on AFIT's Tunable MEMS Cantilever Array Metamaterial -- MEMS for Real-time Infrared Imaging -- New Insights Into Enhancing Microcantilever MEMS Sensors -- A Miniature MRI-compatible Fiber-optic Force Sensor Utilizing Fabry-Perot Interferometer -- Micromechanical Structure With Stable Linear Positive and Negative Stiffness -- Terahertz Metamaterial Structures Fabricated by PolyMUMPs -- Investigations Into 1D and 2D Metamaterials at Infrared Wavelengths -- MEMS Integrated Metamaterials With Variable Resonance Operating at RF Frequencies -- Creep Measurements in Free-standing Thin Metal Film Micro-cantilever Bending -- MEMS Reliability for Space Applications by Elimination of Potential Failure Modes Through Analysis -- Analysis and Evaluation Methods Associated With the Application of Compliant Thermal Interface Materials in Multi-chip Electronic Board Assemblies -- Hierarchical Reliability Model for Life Prediction of Actively Cooled LED-based Luminaire -- Direct Determination of Interfacial Traction-separation Relations in Chip-package Systems.
Keywords: Engineering; Engineering; NANOTECHNOLOGY AND MICROENGINEERING; MECHATRONICS; NANOTECHNOLOGY; NANOTECHNOLOGY